The Nature of Hydrogen in Raney Nickel Catalysts - Nicolau, Ioan (My University, 1975)
The amount and nature of hydrogen in Raney nickel catalysts were determined by various methods: thermal desorption in a volumetric apparatus, temperature-programmed desorption using argon as a carrier gas and techniques similar to those of Amenomiya and Cvetanovic, hydrogen-deuterium exchange, dissolution in acids and other methods. Most of the hydrogen removed in thermal desorption can not be re-adsorbed. Desorption was generally exothermic and each type of sample had a characteristic TPD spectrum. Water vapor, introduced over the catalyst, increased the hydrogen evolution sizeably and this process was also exothermic. Under these conditions water will not oxidize bulk nickel. Present results suggest that the reaction of residual aluminum and water is an important source of hydrogen evolved on heating Raney nickel, but part of the hydrogen is held interstitially.
Keywords: Chemistry; Chemistry